Acute Kidney Injury in Sick Neonate: Incidence and Outcome (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Acute kidney injury (AKI) is an important clinical problem in sick neonate. In most patients, AKI accompanies with a predisposing factor such as sepsis, asphyxia and surgery. The aims of this study were to determine the incidence, associated contributing factors and short term outcome of AKI in hospitalized newborn infants.Materials and Methods: This prospective cohort study was done in Dhaka Shishu Hospital from March 2011 to September 2011. This study included 300 sick neonates admitted during the study period. AKI was defined when serum creatinine level >1.5 mg/dl and BUN was >20 mg/dl on two separate occasions at 24 hours apart. Oliguria was defined as urine output